Iowa Birdline update, September 2, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for September 2, 1991. The highlights for the update include sightings of Western Grebes, a Piping Plover and Red-necked Phalaropes. Also included are handwritten notes with sightings of a Golden-winged Warbler, Yellow-throated Vireo and a Broad-winged Hawk. Epson - sheet feed/flatbed